The Practice of Total Quality Management in Selected Laboratories in Port Harcourt, Nigeria - G. A, Nwankwo,; O, Joel,; O. M. O, Etebu,; G, Abu. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The objective of this study is to determine the extent of total quality management practice in selected laboratories in Rivers State, Nigeria. The data for the study were collected from 600 laboratory personnel using a self-developed, pre-tested, validated and reliable questionnaire. The participants were from the universities, industries, government and private owned medical laboratories. The results were standardized to 100%. The desired extent of total quality management practice was benchmarked at greater than 75%. The results of this study showed that there was below 75% in the extent of total quality management practice in the selected laboratories (59.64±6.72) in Port Harcourt, Nigeria. The extent of total quality management practice was below the expected standard. Efforts should be made to improve the extent of laboratory total quality management in Port Harcourt metropolis, Nigeria. This can be achieved through organized trainings, re-trainings, advocacy, customers and employees focus, and aggressive top management involvement on laboratory total quality management system.